Early is Better: Report of a Cowden Syndrome - Di Nora, A.; Pellino, G.; Di Mari, A.; Scarlata, F.; Greco, F.; Pavone, P. (Global Medical Genetics, 2023)
In the clinical practice, it is not common for pediatricians to visit children with overgrowth phenotype. When it happens, it is important to focus on the age of manifestations and research the pathogenic causes using appropriate genetic test. Cowden syndrome is one of these rare causes; it is an autosomal dominant genodermatosis characterized by multiple hamartomas of ectodermal, mesodermal, and endodermal origin. It is caused by loss of function mutations in the phosphatase and tensin homolog (PTEN) gene located on chromosome 10q23.1 Loss of function of the PTEN gene contributes to overgrowth and risk for a variety of cancers including breast, thyroid, endometrium, skin, kidneys, and colon. The early diagnosis of Cowden disease allows a careful monitoring of the patients who are facing the risk of cancer transformation, which is the principal complication of the condition.
Keywords: overgrowth syndrome; PTEN gene; neuroimaging